Princess Homsia Julia Dumna - Al – zboun, Maen Hamdan Salamh (Journal of Humanities & Social Sciences, 2019)
This study aims at explaining the role of Julia Domena as the head of the Sfeir family، where she had a great influence in the imperial affairs both in the life of her husband and after his death. She was not a normal woman but rather a strong Syrian woman who made a large part of her success، Emperor Roman Emperor، spreading cultural influence in her country، has politically reached high positions. This study was conducted because of the lack of talk about this beautiful princess of thought and the lack of reference scientific studies، and the results reached by Homs center، and when finished (Marcos Orelbos) wars against Zenobia made it a Roman colony، and the financial wealth was large owned by this family، She had a footprint in the Jordan relics in the Roman period and passed through (Julia Domena) where. She suffered a severe injury to her body and suffered from a chest disease (chest cancer) and died. In the light of my talk about the study، a number of the following proposals: shed light on the role of Arab women in the history books more broadly، the development of a simple curriculum taught as a scientific material on the history of some women talked about history.